2020
DOI: 10.5194/tc-14-3407-2020
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing the sensitivity of grounding-line flux to changes in sub-ice-shelf melting

Abstract: Abstract. Using a numerical ice flow model, we study changes in ice shelf buttressing and grounding-line flux due to localized ice thickness perturbations, a proxy for localized changes in sub-ice-shelf melting. From our experiments, applied to idealized (MISMIP+) and realistic (Larsen C) ice shelf domains, we identify a correlation between a locally derived buttressing number on the ice shelf, based on the first principal stress, and changes in the integrated grounding-line flux. The origin of this correlatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…This definition is in line with the original view of buttressing as the backstresses produced by an ice shelf that are felt at the grounding line (Thomas, 1979). This is the approach used in the work of Reese et al (2018) and Zhang et al (2020), who focus on the GLF response to ice-shelf perturbations. We find that the regions with the largest 'buttressing flux response number' (Reese et al, 2018) correspond to the regions providing the majority of the buttressing in our calving experiments.…”
Section: Thinning Experimentsmentioning
confidence: 56%
See 1 more Smart Citation
“…This definition is in line with the original view of buttressing as the backstresses produced by an ice shelf that are felt at the grounding line (Thomas, 1979). This is the approach used in the work of Reese et al (2018) and Zhang et al (2020), who focus on the GLF response to ice-shelf perturbations. We find that the regions with the largest 'buttressing flux response number' (Reese et al, 2018) correspond to the regions providing the majority of the buttressing in our calving experiments.…”
Section: Thinning Experimentsmentioning
confidence: 56%
“…This allowed them to determine the regions in the ice shelf where a perturbation in ice thickness would produce the largest response in GLF, and they also demonstrated that small changes in ice-shelf thickness could impact the GLF hundreds of kilometres away. Finally, Zhang et al (2020) explored the correlation between locally derived buttressing numbers in the ice shelf, and changes in GLF due to small perturbations in ice-shelf thickness at the same locations. They found that for a real-world ice shelf (the LCIS) there was no relationship between these two measures, and that locally derived buttressing numbers are not predictors for the impact of perturbations in ice-shelf geometry on GLF.…”
Section: Introductionmentioning
confidence: 99%
“…This definition is in line with the original view of buttressing as the back stresses produced by an ice shelf that are felt at the grounding line (Thomas, 1979). This is the approach used in the work of Reese et al (2018), Gudmundsson et al (2019) and Zhang et al (2020), who focus on the GLF response to ice-shelf perturbations. We find that the regions with the largest "buttressing flux response number" (Reese In panels (a)-(c) there is a small speed decrease (typically < 10 m a −1 ) at a few computational nodes that is not visible when plotted, and therefore the colour scale has been truncated at zero for clarity.…”
Section: Calving Experiments and Ice-shelf Buttressingmentioning
confidence: 56%
“…The previous work of Reese et al (2018) and Zhang et al (2020) measured the response in GLF to small perturbations in ice-shelf geometry, but by removing the entire ice shelf and calculating the instantaneous response in GLF we are able to quantify the total amount of buttressing that the LCIS provides. This allowed us to examine what proportion of the total buttressing capacity is provided by different regions in the ice shelf.…”
Section: Calving Experiments and Ice-shelf Buttressingmentioning
confidence: 99%
See 1 more Smart Citation